Pengembangan Bahan Ajar Ilmu Pengetahuan Alam Berbasis Model Learning Cycle 7E untuk Siswa Sekolah Dasar - Fembriani Fembriani; Muhamad Taufik Hidayat (Universitas Muhammadiyah Sidoarjo, 2018)
The purpose of this study is to examine the validity of Natural Science teaching materials for fifth grade of elementary school. The development of this teaching material focused on